Circulating Serum Exosomal Long Non-Coding RNAs FOXD2-AS1, NRIR, and XLOC_009459 as Diagnostic Biomarkers for Colorectal Cancer - Yu, Miao; Song, Xing-guo; Zhao, Ya-jing; Dong, Xiao-han; Niu, Li-min; Zhang, Zhi-jun; Shang, Xiao-ling; Tang, You-yong; Song, Xian-rang; Xie, Li (Frontiers in Oncology, 2021)
Background Exosomes derived from cancer cells encapsulate various kinds of tumor-specific molecules and thus can interact with adjacent or distant cells to mediate information exchange. Long non-coding RNAs (lncRNAs) in exosomes have the potential as diagnostic and prognostic biomarkers in different types of cancers. The current study was aimed to identify circulating exosomal lncRNAs for the diagnosis of colorectal cancer (CRC). Methods Exosomes were isolated from the serum by ultracentrifugation and verified by transmission electron microscope (TEM), qNano, and immunoblotting. Exosomal lncRNAs FOXD2-AS1, NRIR, and XLOC_009459 were selected by lncRNA microarray and validated by qPCR in 203 CRC patients and 201 healthy donors. The receiver operating characteristic curve (ROC) was used to assess the diagnostic efficiency of serum exosomal lncRNAs. Results Exosomal FOXD2-AS1, NRIR, and XLOC_009459 (TCONS_00020073) levels were significantly upregulated in 203 CRC patients and 80 early-stage CRC patients compared to 201 healthy donors, possessing the area under the curve (AUC) of 0.728, 0.660, and 0.682 for CRC, as well as 0.743, 0.660, and 0.689 for early-stage CRC, respectively. Notably, their combination demonstrated the markedly elevated AUC of 0.736 for CRC and 0.758 for early-stage CRC, indicating their potential as diagnostic biomarkers for CRC. Conclusions Our data suggested that exosomal lncRNAs FOXD2-AS1, NRIR, and XLOC_009459 act as the promising biomarkers for the diagnostics of CRC and early-stage CRC.